Preparation method of buckwheat hull cellulose nanofiber with controllable size

Through the steps of crushing, enzymatic decomposition, alkaline washing, bleaching and high-pressure homogenization of buckwheat husks, the controllable size of buckwheat husk cellulose nanofibers were prepared, which solved the high cost, serious environmental pollution and uncontrollable size in the existing technology. Problem, efficient and environmentally friendly nanocellulose preparation has been achieved.

CN119433740AActive Publication Date: 2025-02-14SHAANXI NORMAL UNIV
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411512833.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-02-14
Estimated Expiration
2044-10-28

AI Technical Summary

Technical Problem

The existing nanocellulose preparation technology has problems such as high cost, serious environmental pollution and uncontrollable size, especially the long growth cycle of wood and limited supply, and the low utilization rate of agricultural waste.

Method used

Buckwheat husks are used as raw material, and buckwheat husk cellulose nanofibers with controllable size are prepared through steps such as crushing, enzymatic decomposition, alkali washing, bleaching and high-pressure homogenization. The method of combining enzyme pretreatment and high-pressure homogeneity can effectively control the diameter of cellulose in the range of 5~70nm.

Benefits of technology

It realizes efficient conversion from buckwheat husk to cellulose nanofibers, reduces production costs, reduces environmental pollution, and the nanofiber size is controllable and is suitable for different application fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119433740A_ABST
    Figure CN119433740A_ABST
Patent Text Reader

Abstract

The invention provides a green and simple cellulose nanofiber preparation method based on enzyme pretreatment and a high-pressure homogenization technology, belongs to the technical field of nano material preparation, and aims to prepare high-quality cellulose nanofibers with controllable average size from agricultural wastes such as buckwheat hulls and the like. The difficulty and energy consumption of subsequent mechanical treatment are reduced by enzyme pretreatment, and meanwhile, the buckwheat hulls are used as a low-cost raw material, so that the production cost is remarkably reduced; by controlling the number of homogeneous cycles, the average size of the CNF can be flexibly adjusted, and the requirements of different application fields are met; the defects of a traditional preparation method are overcome, resource utilization of agricultural waste is promoted, and remarkable economic benefits and environmental protection value are achieved. The method has a wide prospect in promotion of CNF industrial application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the fields of nanotechnology and material science, and specifically relates to a method for preparing size-controllable buckwheat hull cellulose nanofibers. Background Art

[0002] Cellulose is one of the most abundant and widely distributed natural polymers in nature, accounting for about 50% of natural biological resources and an annual output of about 1.5 trillion tons. As the main component of plant cell walls, cellulose has the advantages of low cost, renewability, and biodegradability, and is mainly used in the papermaking and textile fields. Nanocellulose is the smallest physical structural unit of cellulose and has a "nano effect" that ordinary cellulose does not have, such as excellent mechanical properties, low density, high specific surface area, and rich surface functional groups. It is widely used in biomedicine, environmental protection, optoelectronics, food industry and other industries.

[0003] At present, the main source of nanocellulose is wood, but wood has a long growth cycle and has other important uses such as construction production, so its supply is limited to a certain extent. Agricultural residues, as a potential source of nanocellulose, have the advantages of large output and strong renewability, but their utilization rate is relatively low. Buckwheat husks, as a waste of buckwheat processing, are currently mainly used as pillow fillings, with significantly low added value and serious waste of resources. However, the cellulose content and structure of buckwheat husks are very similar to those of wood, and the growth cycle is short (2-5 months) and the cellulose yield is high. Therefore, the use of buckwheat husks to prepare nanocellulose is an effective source supplement for the production of nanocellulose from wood, and it is also a high value-added utilization of agricultural waste. Therefore, the use of buckwheat husks to prepare nanocellulose is an effective source supplement for the production of nanocellulose from wood, and it is also a high value-added utilization of agricultural waste.

[0004] The technologies for preparing nanocellulose from agricultural waste as raw materials mainly focus on chemical methods (sulfuric acid hydrolysis, 2,2,6,6-tetramethylpiperidinium oxide-mediated oxidation, etc.), mechanical methods (steam explosion, fine grinding, high-pressure homogenization, ultrasonic crushing, etc.) and biological methods. Chemical methods are efficient and mature, but they produce a large amount of acidic wastewater and toxic residues. Although mechanical methods are simple and environmentally friendly, they have limitations such as high energy consumption and uneven particle size distribution of finished products. Undoubtedly, bio-enzymatic hydrolysis is mild and safe, but it is costly, time-consuming and has low yield. Therefore, combining enzymatic hydrolysis with mechanical methods to prepare cellulose nanofibers may benefit from both technologies. Moreover, the use of simple steps and short time-consuming methods to prepare nanocellulose with controllable particle size is a new trend in this field.

[0005] Size control is a key issue in the preparation of nanocellulose. Different application fields have different requirements for the size of nanocellulose, so it is of great significance to develop a method that can accurately control the size of nanocellulose, which can not only improve the performance and quality of the product, but also broaden its application areas. Summary of the invention

[0006] In view of the current technical status that nanocellulose has a single source, high cost for the preparation of nanocellulose, serious environmental pollution and uncontrollable size, the present invention aims to provide a green preparation method for buckwheat hull cellulose nanofibers with controllable size.

[0007] In order to achieve the above object, the technical solution adopted by the present invention is: The present invention provides a method for preparing size-controllable buckwheat hull cellulose nanofibers, comprising: S1, preparation of buckwheat hull cellulose; S2, pre-treating the buckwheat hull cellulose in S1 with enzymes, boiling water bathing, centrifuging, discarding the supernatant, washing, and obtaining a suspension; S3, diluting the buckwheat hull cellulose suspension pretreated by S2 enzyme, and then subjecting it to high pressure homogenization and circulation treatment to obtain size-controlled buckwheat hull cellulose nanofibers.

[0008] In S1, the preparation of buckwheat husk cellulose includes: washing the buckwheat husk, drying it, crushing it, washing it, and enzymolyzing it to obtain enzymolyzed buckwheat; soaking it in alkali solution, adjusting the pH value to 3-4 after treating it with NaClO2 solution, and drying it to obtain buckwheat husk cellulose.

[0009] The enzymatic hydrolysis uses α-amylase, which is added at a mass volume ratio of 0.5% to 0.7%, and the enzymatic hydrolysis is carried out at room temperature for 2h to 4h.

[0010] The enzyme pretreatment uses a cellulose mixed enzyme, the filter paper activity of the cellulose mixed enzyme is 195 FPU / gram, the endoglucanase activity is 2625 U / gram, the β-glucosidase activity is 7196 U / gram, and the xylan endonuclease activity is 2530 U / gram. The cellulose mixed enzyme is added at 0.4% to 0.6% of the substrate mass, and the treatment is carried out at 40-60°C and 250rpm / min for 4-48h.

[0011] Furthermore, in the enzyme pretreatment, cellulose mixed enzyme is added according to 0.5% of the substrate weight, and the treatment is carried out at 50° C. and 250 rpm / min for 24 hours.

[0012] The boiling water bath is treated at 100-120° C. for 10-20 min.

[0013] The high pressure homogenization has a pressure of 300-1000 bar and is performed 10-20 times.

[0014] Furthermore, the high-pressure homogenization treatment is carried out at a pressure of 300 bar for 2-10 times; at a pressure of 600 bar for 2-10 times; at a pressure of 900 bar for 2-10 times; and at a pressure of 1000 bar for 2-10 times.

[0015] The present invention provides size-controlled buckwheat husk cellulose nanofibers obtained by the preparation method of the size-controlled buckwheat husk cellulose nanofibers. The size-controlled buckwheat husk cellulose nanofibers are derived from buckwheat husk cellulose, and the diameter of the buckwheat husk cellulose nanofibers can be controlled within the range of 5 to 70 nm.

[0016] Furthermore, the diameter of the buckwheat hull cellulose nanofibers can be controlled within the range of 20 to 40 nm.

[0017] The present invention provides application of the size-controllable buckwheat hull cellulose nanofibers in stabilizing emulsions.

[0018] Compared with the prior art, the beneficial effects of the present invention are: The preparation method provided by the present invention uses buckwheat husks as raw materials, and realizes the efficient conversion from buckwheat husks to cellulose nanofibers through the steps of crushing, alcohol washing, enzymolysis, alkali washing, bleaching and high-pressure homogenization. The entire process is relatively simple and easy to promote and apply in industry; the agricultural waste buckwheat husks are converted into high-value-added nanomaterials, the raw material sources are wide and the price is low, the resource utilization of waste is realized, and the production cost is effectively reduced; through enzymatic pretreatment, the cellulose mixed enzyme specifically acts on the cellulose molecular chain, reducing the crystallinity and polymerization degree of cellulose, the connection between the cellulose molecular chains is partially interrupted, and the fiber structure is exposed and loosened to a certain extent, which is helpful to achieve fiber refinement and peeling in the subsequent high-pressure homogenization process. At the same time, this step can accelerate the decomposition process of cellulose, reduce the time and energy consumption required for subsequent processing, thereby improving the overall processing efficiency; by adjusting the pressure and number of cycles of high-pressure homogenization, the cellulose pretreated by the enzyme can be further refined. The cellulose nanofibers can be made more uniform and dispersed in the solution, avoiding the agglomeration and precipitation of the fibers, thereby improving the utilization rate and performance of the fibers; the enzymatic pretreatment combined with the high-pressure homogenization treatment has a synergistic effect, effectively exposing the fiber structure, promoting the refinement and peeling of the fibers, and can accurately control the diameter of the cellulose nanofibers within the range of 5 to 70 nm, which can be more finely regulated to 20 to 40 nm. This size controllability enables the cellulose nanofibers to have a high specific surface area, good biocompatibility and degradability, etc., providing greater flexibility for their application in different fields; compared with traditional chemical treatment methods, the method provided by the present invention is more environmentally friendly and easy to control, and can further reduce production costs by optimizing process parameters and improving treatment efficiency.

[0019] The present invention provides size-controllable buckwheat hull cellulose nanofibers, the diameter of the cellulose nanofibers is in the range of 5 to 70 nm, the buckwheat hull cellulose nanofibers have a high specific surface area, good biocompatibility and degradability, and can accurately control the stability of food emulsions of different compositions. The buckwheat hull cellulose nanofibers can be used as an emulsifier or stabilizer, and are wrapped on the surface of oil droplets or water droplets by physical adsorption or chemical bonding to form a protective layer, thereby preventing the occurrence of emulsion stratification, flocculation and the like; they can form a uniform dispersion system in food without causing obvious granularity, and can interact more with other ingredients in food, thereby helping to improve the taste and texture of food, and can also improve the nutritional value of food and extend the shelf life of food; their good biocompatibility means that they will not induce immune or toxic reactions in the human body, and can be safely used in food, and are an ideal food additive or functional ingredient. The invention discloses a novel food product with a unique taste, texture and nutritional value, and has the advantages of being safe, healthy, environmentally friendly and sustainable, and having a large application prospect and a huge market potential in the food industry. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 The scanning electron microscope images of cellulose prepared under different conditions of the present invention, wherein A is Example 3, A-1, A-2 and A-3 are at different magnifications; B is Example 5, B-1, B-2 and B-3 are at different magnifications; C is Example 6, C-1, C-2 and C-3 are at different magnifications; D is Example 7, D-1, D-2 and D-3 are at different magnifications; FIG2 is an atomic force microscope image and diameter distribution histogram of nanocellulose fibers prepared under different embodiments of the present invention, wherein: Figure 2A is Example 3, A-1 and A-2 are different magnifications, and A-3 is the particle size distribution; Figure 2B is Example 5, B-1 and B-2 are different magnifications, and B-3 is the particle size distribution; Figure 2C is Example 6, C-1 and C-2 are different magnifications, and C-3 is the particle size distribution; Figure 2D is Example 7, D-1 and D-2 are different magnifications, and D-3 is the particle size distribution; Figure 2E This is Example 8, E-1 and E-2 are different magnifications, and E-3 is the particle size distribution.

[0021] Figure 3 These are images of the emulsion of nanocellulose fiber loaded with citral essential oil prepared under the conditions of different embodiments of the present invention stored for 15 days, wherein A is Example 3, A-1 is a CNF addition concentration of 0.15%, and A-2 is a CNF addition concentration of 0.35%; B is Example 5, B-1 is a CNF addition concentration of 0.15%, and B-2 is a CNF addition concentration of 0.35%; C is Example 6, C-1 is a CNF addition concentration of 0.15%, and C-2 is a CNF addition concentration of 0.35%; D is Example 7, D-1 is a CNF addition concentration of 0.15%, and D-2 is a CNF addition concentration of 0.35%; E is Example 8, E-1 is a CNF addition concentration of 0.15%, and E-2 is a CNF addition concentration of 0.35%. DETAILED DESCRIPTION

[0022] In order to enable those skilled in the art to better understand the scheme of the present invention, the technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0023] The present invention is described in further detail below: Example 1 1) Preparation of buckwheat husk cellulose: Buckwheat husks were repeatedly rinsed with tap water, dried in an oven at 45°C for 24 h, crushed and sieved through a 100-mesh sieve to obtain buckwheat husk powder, which was stored in a dry place for later use; Buckwheat husk cellulose (BP) was washed with anhydrous ethanol for 5 h and repeated twice at room temperature (25°C), then rinsed with deionized water and dried; The obtained sample was added to a 0.6% (w / v) α-amylase solution prepared in advance for enzymatic hydrolysis for 3 h; After rinsing and drying, it was immersed in a 5% (w / v) NaOH solution, stirred at 70°C for 2 h and repeated twice to remove hemicellulose and other non-cellulose components; Finally, the sample was added to a 1.5% (w / v) NaClO2 solution, and the pH was adjusted to 3-4 with acetic acid, stirred at 70°C for 2 h, repeated 4 times, to remove lignin and other pigments, and a white cellulose sample was obtained; The white sample was washed with a large amount of deionized water until neutral, and dried in an oven at 45°C for 24 h to obtain buckwheat husk cellulose. The solid-to-liquid ratio for all steps was 1:20 (m / v).

[0024] 2) Enzyme pretreatment: Buckwheat husk cellulose was dispersed in 50 mmol / L sodium acetate buffer (pH=4.8) at a solid loading of 4% (w / v), and cellulose mixed enzymes with a concentration of 5 mg protein / g fiber substrate were added; after mixing evenly, the mixture was reacted at an enzymatic hydrolysis temperature of 50°C and a shaking speed of 250 rpm / min for 4 h; the mixture was placed in a 100°C boiling water bath for 15 min to inactivate the enzyme; it was centrifuged at 4000 rpm for 15 min to separate the supernatant containing the enzymatic hydrolysis product and the solid precipitate, and the supernatant was discarded; the precipitate was repeatedly washed and centrifuged with deionized water for 4 times to remove residual enzymes and biomass products.

[0025] Example 2 1) Preparation of buckwheat husk cellulose: Buckwheat husks were repeatedly rinsed with tap water, dried in an oven at 45°C for 24 h, crushed and sieved through a 100-mesh sieve to obtain buckwheat husk powder, which was stored in a dry place for later use. Buckwheat husk cellulose (BP) was washed with anhydrous ethanol for 5 h and repeated twice at room temperature (25°C), then rinsed with deionized water and dried. The obtained sample was added to a 0.6% (w / v) α-amylase solution prepared in advance for enzymatic hydrolysis for 3 h; after rinsing and drying, it was immersed in a 5% (w / v) NaOH solution and stirred at 70°C for 2 h and repeated twice. Finally, the obtained sample was added to a 1.5% (w / v) NaClO2 solution, the pH was adjusted to 3-4 with acetic acid, and stirred at 70°C for 2 h; this step was repeated 4 times, and the white sample was washed with a large amount of deionized water until neutral, and placed in an oven at 45°C for 24 h to obtain buckwheat husk cellulose; the solid-liquid ratio of all the above steps was 1:20 (m / v).

[0026] 2) Enzyme pretreatment: Buckwheat hull cellulose was dispersed in 50 mmol / L sodium acetate buffer (pH=4.8) with a solid loading of 4% (w / v), and cellulose mixed enzymes were added at 5 mg protein / g fiber substrate; after mixing evenly, enzymatic hydrolysis was carried out on a shaker at 50°C and 250 rpm for 12 h; the mixture was placed in a 100°C boiling water bath for 15 min to inactivate the enzyme, and then centrifuged at 4000 rpm for 15 min to discard the supernatant, and the solid precipitate after enzymatic hydrolysis was separated by centrifugation, washed with deionized water and centrifuged, and the operation was repeated 4 times to remove residual enzymes and biomass products.

[0027] Example 3 1) Preparation of buckwheat husk cellulose: Buckwheat husks were repeatedly rinsed with tap water, dried in an oven at 45°C for 24 h, crushed and sieved through a 100-mesh sieve to obtain buckwheat husk powder, which was stored in a dry place for later use. BP was washed with anhydrous ethanol for 5 h and repeated twice at room temperature (25°C), then rinsed with deionized water and dried. The obtained sample was added to the 0.6% (w / v) α-amylase solution prepared in advance for enzymatic hydrolysis for 3 h. After rinsing and drying, it was immersed in a 5% (w / v) NaOH solution and stirred at 70°C for 2 h and repeated twice. Finally, the obtained sample was added to a 1.5% (w / v) NaClO2 solution, and the pH was adjusted to 3-4 with acetic acid, and stirred at 70°C for 2 h. After this step was repeated 4 times, the white sample was washed with a large amount of deionized water until neutral, and dried in an oven at 45°C for 24 h to obtain buckwheat husk cellulose. The solid-liquid ratio of all steps was 1:20 (m / v).

[0028] 2) Enzyme pretreatment: Buckwheat hull cellulose was dispersed in 50 mmol / L sodium acetate buffer (pH 4.8) at a solid loading of 4% (w / v), and cellulose mixed enzymes with 5 mg protein / g fiber substrate were added. After mixing evenly, the mixture was reacted at an enzymatic hydrolysis temperature of 50°C and a shaking speed of 250 rpm / min for 24 h. The mixture was placed in a boiling water bath at 100°C for 15 min to inactivate the enzyme. It was then centrifuged at 4000 rpm for 15 min and the supernatant was discarded. To remove enzyme impurities and biomass products, the precipitate was washed with deionized water and centrifuged, and the operation was repeated 4 times.

[0029] Example 4 1) Preparation of buckwheat husk cellulose: Buckwheat husks were repeatedly rinsed with tap water, dried in an oven at 45°C for 24 h, crushed and sieved through a 100-mesh sieve to obtain buckwheat husk powder, which was stored in a dry place for later use. BP was washed with anhydrous ethanol for 5 h and repeated twice at room temperature (25°C), then rinsed with deionized water and dried. The obtained sample was added to the 0.6% (w / v) α-amylase solution prepared in advance for enzymatic hydrolysis for 3 h. After rinsing and drying, it was immersed in a 5% (w / v) NaOH solution and stirred at 70°C for 2 h and repeated twice. Finally, the obtained sample was added to a 1.5% (w / v) NaClO2 solution, and the pH was adjusted to 3-4 with acetic acid, and stirred at 70°C for 2 h. After this step was repeated 4 times, the white sample was washed with a large amount of deionized water until neutral, and dried in an oven at 45°C for 24 h to obtain buckwheat husk cellulose. The solid-liquid ratio of all steps was 1:20 (m / v).

[0030] 2) Enzyme pretreatment: Buckwheat hull cellulose was dispersed in 50 mmol / L sodium acetate buffer (pH 4.8) at a solid loading of 4% (w / v), and cellulose mixed enzymes with 5 mg protein / g fiber substrate were added. After mixing evenly, the mixture was reacted at an enzymatic hydrolysis temperature of 50°C and a shaking speed of 250 rpm / min for 48 h. The mixture was placed in a 100°C boiling water bath for 15 min to inactivate the enzyme. It was then centrifuged at 4000 rpm for 15 min and the supernatant was discarded; to remove enzyme impurities and biomass products, the precipitate was washed with deionized water and centrifuged, and the operation was repeated 4 times.

[0031] Example 5 1) Preparation of buckwheat husk cellulose: Buckwheat husks were repeatedly rinsed with tap water, dried in an oven at 45°C for 24 h, crushed and sieved through a 100-mesh sieve to obtain buckwheat husk powder, which was stored in a dry place for later use. BP was washed with anhydrous ethanol for 5 h and repeated twice at room temperature (25°C), then rinsed with deionized water and dried. The obtained sample was added to a 0.6% (w / v) α-amylase solution prepared in advance for enzymatic hydrolysis for 3 h. After rinsing and drying, it was immersed in a 5% (w / v) NaOH solution and stirred at 70°C for 2 h and repeated twice. Finally, the obtained sample was added to a 1.5% (w / v) NaClO2 solution, and the pH was adjusted to 3-4 with acetic acid, and stirred at 70°C for 2 h. After this step was repeated 4 times, the white sample was washed with a large amount of deionized water until neutral, and dried in an oven at 45°C for 24 h to obtain buckwheat husk cellulose. The solid-liquid ratio of all steps was 1:20 (m / v).

[0032] 2) Enzyme pretreatment: Buckwheat hull cellulose was dispersed in 50 mmol / L sodium acetate buffer (pH=4.8) at a solid loading of 4% (w / v), and cellulose mixed enzymes with 5 mg protein / g fiber substrate were added. After mixing evenly, the mixture was reacted at an enzymatic hydrolysis temperature of 50°C and a shaking speed of 250 rpm / min for 24 h. The mixture was placed in a 100°C boiling water bath for 15 min to inactivate the enzyme. It was then centrifuged at 4000 rpm for 15 min and the supernatant was discarded. To remove enzyme impurities and biomass products, the precipitate was washed with deionized water and centrifuged, and the operation was repeated 4 times.

[0033] 3) High-pressure homogenization treatment: The suspension obtained by enzyme pretreatment was diluted with deionized water to 1% (w / v). It was treated once with a high-pressure homogenizer at a pressure of 300 bar to obtain cellulose nanofibers.

[0034] Example 6 1) Preparation of buckwheat husk cellulose: Buckwheat husks were repeatedly rinsed with tap water, dried in an oven at 45°C for 24 h, crushed and sieved through a 100-mesh sieve to obtain buckwheat husk powder, which was stored in a dry place for later use. BP was washed with anhydrous ethanol for 5 h and repeated twice at room temperature (25°C), then rinsed with deionized water and dried. The obtained sample was added to the 0.6% (w / v) α-amylase solution prepared in advance for enzymatic hydrolysis for 3 h. After rinsing and drying, it was immersed in a 5% (w / v) NaOH solution and stirred at 70°C for 2 h and repeated twice. Finally, the obtained sample was added to a 1.5% (w / v) NaClO2 solution, and the pH was adjusted to 3-4 with acetic acid, and stirred at 70°C for 2 h. After this step was repeated 4 times, the white sample was washed with a large amount of deionized water until neutral, and dried in an oven at 45°C for 24 h to obtain buckwheat husk cellulose. The solid-liquid ratio of all steps was 1:20 (m / v).

[0035] 2) Enzyme pretreatment: Buckwheat hull cellulose was dispersed in 50 mmol / L sodium acetate buffer (pH 4.8) at a solid loading of 4% (w / v), and cellulose mixed enzymes with 5 mg protein / g fiber substrate were added. After mixing evenly, the mixture was reacted at an enzymatic hydrolysis temperature of 50°C and a shaking speed of 250 rpm / min for 24 hours. The mixture was placed in a boiling water bath at 100°C for 15 minutes to inactivate the enzyme. It was then centrifuged at 4000 rpm for 15 minutes and the supernatant was discarded. To remove enzyme impurities and biomass products, the precipitate was washed with deionized water and centrifuged, and the operation was repeated 4 times.

[0036] 3) High-pressure homogenization: The suspension obtained by enzyme pretreatment was diluted with deionized water to 1% (w / v). The suspension was treated with a high-pressure homogenizer at a pressure of 300 bar for 3 times and at a pressure of 600 bar for 2 times to obtain cellulose nanofibers.

[0037] Example 7 1) Preparation of buckwheat husk cellulose: Buckwheat husks were repeatedly rinsed with tap water, dried in an oven at 45°C for 24 h, crushed and sieved through a 100-mesh sieve to obtain buckwheat husk powder, which was stored in a dry place for later use. BP was washed with anhydrous ethanol for 5 h and repeated twice at room temperature (25°C), then rinsed with deionized water and dried. The obtained sample was added to the 0.6% (w / v) α-amylase solution prepared in advance for enzymatic hydrolysis for 3 h. After rinsing and drying, it was immersed in a 5% (w / v) NaOH solution and stirred at 70°C for 2 h and repeated twice. Finally, the obtained sample was added to a 1.5% (w / v) NaClO2 solution, and the pH was adjusted to 3-4 with acetic acid, and stirred at 70°C for 2 h. After this step was repeated 4 times, the white sample was washed with a large amount of deionized water until neutral, and dried in an oven at 45°C for 24 h to obtain buckwheat husk cellulose. The solid-liquid ratio of all steps was 1:20 (m / v).

[0038] 2) Enzyme pretreatment: Buckwheat hull cellulose was dispersed in 50 mmol / L sodium acetate buffer (pH 4.8) at a solid loading of 4% (w / v), and cellulose mixed enzymes with 5 mg protein / g fiber substrate were added. After mixing evenly, the mixture was reacted at an enzymatic hydrolysis temperature of 50°C and a shaking speed of 250 rpm / min for 24 hours. The mixture was placed in a boiling water bath at 100°C for 15 minutes to inactivate the enzyme. It was then centrifuged at 4000 rpm for 15 minutes and the supernatant was discarded. To remove enzyme impurities and biomass products, the precipitate was washed with deionized water and centrifuged, and the operation was repeated 4 times.

[0039] 3) High-pressure homogenization: The suspension obtained by enzyme pretreatment was diluted with deionized water to 1% (w / v). The suspension was treated with a high-pressure homogenizer at a pressure of 300 bar for 3 times, 600 bar for 3 times, 900 bar for 3 times, and 1000 bar for 1 time to obtain cellulose nanofibers.

[0040] Example 8 1) Preparation of buckwheat husk cellulose: Buckwheat husks were repeatedly rinsed with tap water, dried in an oven at 45°C for 24 h, crushed and sieved through a 100-mesh sieve to obtain buckwheat husk powder, which was stored in a dry place for later use. BP was washed with anhydrous ethanol for 5 h and repeated twice at room temperature (25°C), then rinsed with deionized water and dried. The obtained sample was added to the 0.6% (w / v) α-amylase solution prepared in advance for enzymatic hydrolysis for 3 h. After rinsing and drying, it was immersed in a 5% (w / v) NaOH solution and stirred at 70°C for 2 h and repeated twice. Finally, the obtained sample was added to a 1.5% (w / v) NaClO2 solution, and the pH was adjusted to 3-4 with acetic acid, and stirred at 70°C for 2 h. After this step was repeated 4 times, the white sample was washed with a large amount of deionized water until neutral, and dried in an oven at 45°C for 24 h to obtain buckwheat husk cellulose. The solid-liquid ratio of all steps was 1:20 (m / v).

[0041] 2) Enzyme pretreatment: Buckwheat hull cellulose was dispersed in 50 mmol / L sodium acetate buffer (pH 4.8) at a solid loading of 4% (w / v), and cellulose mixed enzymes with 5 mg protein / g fiber substrate were added. After mixing evenly, the mixture was reacted at an enzymatic hydrolysis temperature of 50°C and a shaking speed of 250 rpm / min for 24 hours. The mixture was placed in a boiling water bath at 100°C for 15 minutes to inactivate the enzyme. It was then centrifuged at 4000 rpm for 15 minutes and the supernatant was discarded. To remove enzyme impurities and biomass products, the precipitate was washed with deionized water and centrifuged, and the operation was repeated 4 times.

[0042] 3) High-pressure homogenization: The suspension obtained by enzyme pretreatment was diluted with deionized water to 1% (w / v). A high-pressure homogenizer was used to treat it at a pressure of 300 bar for 6 times, 600 bar for 6 times, 900 bar for 6 times, and 1000 bar for 2 times to obtain cellulose nanofibers.

[0043] Figure 1 Scanning electron microscope images of microcellulose prepared by different enzymatic pretreatment times. Figure 1 It can be concluded that for Example 1, when the enzymatic hydrolysis time is 4 h, the fibers are separated layer by layer in rectangular sheets, and bulges and wrinkles appear on the surface. This is because the amorphous regions where the cellulose chains tend to be parallel oriented and randomly distributed are first destroyed by the enzyme; this indicates that in a shorter enzymatic hydrolysis time, the cellulose mixed enzyme first attacks the amorphous regions in the cellulose chains, which are more easily destroyed by the enzyme due to the parallel orientation and disordered distribution of the cellulose chains. However, due to the short time, the enzymatic hydrolysis has not yet fully penetrated into the deeper layers or crystalline regions of the fibers.

[0044] For Example 2, when the enzymatic hydrolysis time was 12 h, as the enzymatic hydrolysis time was maintained, the hierarchical structure of the fiber allowed the enzyme to contact more action sites, thereby promoting the in-depth enzymatic hydrolysis reaction. This layer-by-layer unidirectional hydrolysis method led to further thinning of the fiber and the appearance of surface fibrils, indicating that the enzymatic hydrolysis efficiency was improved.

[0045] For Example 3, during the 24-hour enzymatic hydrolysis, the cellulose mixed enzymes fully synergized and not only destroyed the amorphous region of the fiber, but also successfully penetrated into the crystalline region, randomly cutting the β-1,4-glycosidic bonds, resulting in the fibrillation and breakage of the fiber. This deep enzymatic hydrolysis caused a significant change in the fiber morphology, forming a network structure of microfibrils intertwined with each other, which is conducive to subsequent processing and application.

[0046] For Example 4, when the time is extended to 48 h, the fibrils are basically not visible, and the whole is in the form of particles or agglomerated particles. This is because the hydrolysis time is too long, the cellulase over-cuts the cellulose molecules, and it is easy to self-assemble through the interfacial hydrogen bonds to form spherical fiber particles of different sizes. Too long enzymatic hydrolysis time causes cellulase to over-cut the cellulose molecules, destroying the integrity of the fiber. The fiber fragments self-assemble through interfacial hydrogen bonds to form spherical fiber particles of different sizes. This structure may not be conducive to certain application requirements, such as the preparation of reinforced materials or the realization of specific biological functions.

[0047] Based on the above analysis, Example 3 showed the best pretreatment effect when the enzymatic hydrolysis time was 24 h. Under this condition, the cellulose mixed enzyme can effectively penetrate into the fiber, destroying the amorphous region and cutting the β-1,4-glycosidic bonds in the crystalline region, achieving the fibrillation and breakage of the fiber, and forming a microfibril network structure that is beneficial to subsequent applications. Therefore, the pretreatment conditions of Example 3 are of great significance for the preparation of microcellulose materials with excellent properties.

[0048] FIG2 is an atomic force microscope image and a diameter distribution histogram of nanocellulose fibers prepared under different example conditions.

[0049] It can be seen from the data in Figure 2 that in Figure 2, A is Example 3, B is Example 5, C is Example 6, D is Example 7, and E is Example 8. Changes in fiber morphology: As the number of high-pressure homogenization increases, the fibers gradually tear and peel off along the longitudinal direction. This is because during the high-pressure homogenization process, the cellulose fibers are placed under extremely high pressure. When they pass through the slit, the pressure is released instantly, resulting in strong shear and tensile forces inside the fibers, causing the fibers to tear and peel off; this tearing and peeling process actually promotes the nanofibrillation of the fibers, that is, the fibers are refined into smaller nanoscale units. As the number of homogenization increases, the degree of fiber refinement gradually increases, and eventually nanocellulose fibers with finer diameters and more uniform distribution are obtained.

[0050] Diameter distribution changes The diameter distribution narrows and shifts to the left: It can be seen from the diameter distribution histogram that as the number of high-pressure homogenization increases, the diameter distribution of cellulose nanofibers gradually narrows and shifts to the left. This means that the diameter range of the fibers is more concentrated, and the average diameter gradually decreases. This is because fibers with larger diameters are more easily torn and refined during high-pressure homogenization, thereby reducing the overall average diameter. Example 7, when the number of homogenizations is 10 times, about 48% of the cellulose nanofibers have a diameter of 25~35nm, and the average diameter is 28.04 ± 0.90 nm, which shows that after 10 homogenizations, the fibers have been well refined, but a considerable portion of the fibers still have a larger diameter. Example 8, when the number of homogenizations is increased to 20 times, about 40% of the cellulose nanofibers have a diameter of 15~20nm, and the average diameter is 17.93 ± 0.42 nm, which shows that after increasing to 20 homogenizations, the degree of fiber refinement is significantly improved, the proportion of fibers with smaller diameters increases, and the average diameter is significantly reduced.

[0051] In summary, the number of high-pressure homogenization times has a significant effect on the morphology and diameter distribution of nanocellulose fibers. As the number of homogenization times increases, the fibers gradually achieve nanofibrillation, the diameter distribution becomes narrower and shifts to the left, and the average diameter decreases. For application scenarios where nanocellulose fibers with smaller diameters and more uniform distributions need to be prepared (such as high-performance composite materials, biomedical materials, etc.), increasing the number of high-pressure homogenization times is an effective means. In this example, Example 8 showed a better nanofibrillation effect when the number of homogenization times was 20.

[0052] The yield and average diameter of the nanocellulose prepared under different conditions were further statistically analyzed, see Table 1 for details.

[0053] Table 1 shows the yield and average diameter of nanocellulose fibers prepared under different conditions.

[0054] Different superscript letters in the same column indicate significant differences among groups (P<0.05) From the data in Table 1, we can see that the yield analysis shows that as the number of homogenization cycles increases, the yield of CNF shows a certain degree of downward trend. From Example 5 to Example 8, the number of homogenization cycles increases, while the yield gradually decreases from 26.15% to 22.29%. This is because during the multiple homogenization processes, some cellulose fibers are over-refined or degraded, resulting in a reduction in the quality of CNF that can be collected. Although the yield has decreased, even the lowest yield (22.29%) is better than the yield reported by a single method. This shows that the combined method of enzymatic hydrolysis and high-pressure homogenization has significant advantages in improving the efficiency of CNF production. This method may reduce the crystallinity and degree of polymerization of cellulose through enzymatic pretreatment, making the subsequent high-pressure homogenization process more efficient.

[0055] Average diameter analysis: With the increase of homogenization cycles, the average diameter of CNF decreased significantly, from 49.98 nm in Example 5 to 17.93 nm in Example 8, which shows that multiple homogenizations can effectively refine cellulose fibers into smaller nanoscale units; the reduction in average diameter is not only conducive to the application of CNF in composite materials, biomedical materials and other fields, but also reflects the effectiveness of enzymatic hydrolysis combined with high-pressure homogenization in promoting cellulose nanofiberization.

[0056] In summary, enzymatic hydrolysis combined with high-pressure homogenization is an effective method for preparing CNF. This method not only conforms to the concept of green environmental protection, but also can significantly reduce the average diameter of CNF while maintaining a high yield, thereby improving production efficiency. Future research should focus on further optimizing process parameters to achieve higher yields and better CNF quality.

[0057] Figure 3 The images of the emulsions of nanocellulose fibers loaded with citral essential oil prepared under different embodiments of the present invention are shown in Figure 1. In order to verify the stable emulsification performance of nanocellulose prepared under different embodiments of the present invention, the emulsions were prepared with citral as the oil phase (10%, v / v) and CNF suspension as the water phase (90%, v / v). The final concentrations of CNF were 0.15 and 0.35% (w / v), respectively.

[0058] By the attached Figure 3 The data shows that Figure 3In the figure, A is Example 3, B is Example 5, C is Example 6, D is Example 7, E is Example 8, -1 is a CNF addition concentration of 0.15%, and -2 is a CNF addition concentration of 0.35%. Since the emulsion is a thermodynamically unstable system, after being stored at room temperature for 15 days, the emulsion showed obvious phase separation. The less water phase layer appears at the bottom, the more stable the emulsion. It can be intuitively observed that the smaller the diameter of the CNF, the better the emulsion stability, because smaller CNF particles can more effectively wrap and stabilize oil droplets. At the same time, as the CNF concentration increases, the effect of stabilizing essential oils also improves. At the same CNF diameter, a CNF concentration of 0.35% can stabilize the emulsion better than a CNF concentration of 0.15%.

[0059] This experiment verified the stable emulsification performance of CNF by preparing CNF-loaded citral essential oil emulsions under different conditions and observing their stability after 15 days of storage at room temperature. The results showed that the diameter and concentration of CNF had a significant effect on the stability of the emulsion. Smaller CNF diameters and higher CNF concentrations can more effectively stabilize the essential oil emulsion.

[0060] The above contents are only for explaining the technical idea of ​​the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.

Claims

1. A method for preparing size-controlled buckwheat hull cellulose nanofibers, characterized in that: include: S1, preparation of buckwheat hull cellulose; S2, performing enzyme pretreatment on buckwheat hull cellulose, boiling water bathing, centrifuging, discarding supernatant, washing, and obtaining a buckwheat hull cellulose suspension after enzyme pretreatment; S3, diluting the enzyme pretreated buckwheat hull cellulose suspension, and then subjecting it to high pressure homogenization and circulation treatment to obtain size-controlled buckwheat hull cellulose nanofibers.

2. The method for preparing size-controlled buckwheat hull cellulose nanofibers according to claim 1, characterized in that: In S1, the preparation of buckwheat husk cellulose includes: washing the buckwheat husk, drying it, crushing it, washing it, and enzymolyzing it to obtain enzymolyzed buckwheat; soaking it in alkali solution, adjusting the pH value to 3-4 after treating it with NaClO2 solution, and drying it to obtain buckwheat husk cellulose.

3. The method for preparing size-controlled buckwheat hull cellulose nanofibers according to claim 2, characterized in that: The enzymatic hydrolysis uses α-amylase, which is added at a mass volume ratio of 0.5% to 0.7%, and the enzymatic hydrolysis is performed at room temperature for 2h to 4h.

4. The method for preparing size-controlled buckwheat hull cellulose nanofibers according to claim 1, characterized in that: The enzyme pretreatment uses a cellulose mixed enzyme, the filter paper activity of the cellulose mixed enzyme is 195 FPU / gram, the endoglucanase activity is 2625 U / gram, the β-glucosidase activity is 7196 U / gram, and the xylan endonuclease activity is 2530 U / gram. The cellulose mixed enzyme is added at 0.4% to 0.6% of the substrate mass, and the treatment is carried out at 40-60°C and 250 rpm / min for 4-48 hours.

5. The method for preparing size-controlled buckwheat hull cellulose nanofibers according to claim 4, characterized in that: In the enzyme pretreatment, cellulose mixed enzyme was added at 0.5% of the substrate weight, and the treatment was carried out at 50° C. and 250 rpm / min for 24 hours.

6. The method for preparing size-controlled buckwheat hull cellulose nanofibers according to claim 1, characterized in that: The boiling water bath is treated at 100-120° C. for 10-20 min.

7. The method for preparing size-controlled buckwheat hull cellulose nanofibers according to claim 1, characterized in that: The high pressure homogenization has a pressure of 300-1000 bar and is performed 10-20 times.

8. The method for preparing size-controlled buckwheat hull cellulose nanofibers according to claim 7, characterized in that: The high pressure homogenization treatment is carried out at a pressure of 300 bar for 2-10 times; at a pressure of 600 bar for 2-10 times; at a pressure of 900 bar for 2-10 times; and at a pressure of 1000 bar for 2-10 times.

9. The size-controlled buckwheat husk cellulose nanofibers obtained by the method for preparing size-controlled buckwheat husk cellulose nanofibers according to any one of claims 1 to 8, characterized in that: The size-controllable buckwheat husk cellulose nanofibers are derived from buckwheat husk cellulose, and the diameter of the buckwheat husk cellulose nanofibers can be controlled within the range of 5 to 70 nm.

10. Use of the size-controllable buckwheat husk cellulose nanofibers according to claim 9 in stabilizing emulsions.

Citation Information

Patent Citations

  • Method for preparing wheat straw cellulose microfibrils by auxiliary enzymatic pretreatment

    CN106436414A

  • Preparation method of rice bran dietary fiber nano powder

    CN108813641A

  • Method for preparing peanut shell nanocellulose through combination of steam explosion with high-pressure homogenization

    CN109338781A

  • Plant cellulose nanofibril and green preparation method thereof

    CN112376305A

  • Method for preparing lignin-containing cellulose nanofibrils

    CN112709090A